Weird but true! 3 300 outrageous facts. - National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2011)
Offers a collection of true facts about animals, food, science, pop culture, outer space, geography, and weather.
OSLIS\Gale Nat Geo eBooks(2/2/23).
"National Geographic Kids."
Includes index.
Description based on print version record.
Keywords: Curiosities and wonders -- Juvenile literature; Curiosities and wonders; Electronic books- OSLIS; Electronic books